Chronic pelvic pain in endometriosis: from therapeutic Abstraction to clinical definition: A review - Mekan R. Orazov; Viktor E. Radzinski; Evgeny D. Dolgov (IP Berlin A.V., 2023)
Currently, endometriosis is one of the most common and relevant gynecological conditions. It is characterized by a wide range of symptoms, with highly heterogeneous pain being one of the most typical. The unifying concept of the algological patterns of endometriosis is chronic pelvic pain, which contributes to a pronounced decrease in patients' quality of life. Therefore, it is necessary to analyze the key pathogenetic mechanisms of pelvic pain associated with endometriosis and to determine a personalized therapeutic approach based on them.